The scenario of urban vegetable gardens of Londrina: Challenges and potentialities in the promotion of sustainable cities - Antonello, Ideni Terezinha; Veiga, Léia Aparecida; Alievi, Alan Alves (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
Having as central theme the urban gardens, the aim of this research was to present aspects concerning the urban vegetable gardens of Londrina to enter the discussion of the challenges and potentialities that this form of social organization of food production can contribute to create mechanisms and strategies aimed at the struggle for the crystallization of sustainable cities and communities. The methodological procedures were based on secondary (scientific production, documents and official websites) and primary (simple observation and visit to a municipal school) sources of information.  It was found that urban vegetable gardens in Londrina, whether in the community format or in municipal schools, have relevance in the context of building sustainable communities in the city. In Londrina the vegetable gardens have involved technicians, students, education professionals, neighborhood residents in a process of resumption of a practice that can contribute to minimize the impact of hunger among families with lower purchasing power and also contribute to the care of the environment.
Keywords: Urban Agriculture; Food; Environmental Education